2023
DOI: 10.1029/2022jb026136
|View full text |Cite
|
Sign up to set email alerts
|

Development of Amphibole Crystal Preferred Orientations (CPOs) and Their Effects on Seismic Anisotropy in Deformed Amphibolites

Abstract: Crystal preferred orientations and seismic anisotropy of amphibole play a crucial role in fingerprinting the rheological and physical properties of the deep crust. This study presents typical naturally deformed (banded, mylonitic, and ultramylonitic) amphibolites from the Ailao Shan‐Red River shear zone (ASRR‐SZ), southwestern China. In the banded amphibolite, coarse amphibole grains are highly elongated by dislocation creep and develop type I fabric of amphibole. In the mylonitic amphibolite, amphibole grains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 88 publications
2
5
0
Order By: Relevance
“…This transition in the Vp pattern is accompanied by increased density of the [100] and [010] crystallographic axes in the Z‐ and Y‐directions respectively that implies a transition between the type‐IV and type‐I amphibole CPOs in these samples. The magnitude of AVp percentages of the blueschists in our compilation can be broadly ordered as AVp(Vp‐pattern I) > AVp(Vp‐pattern III) > AVp(Vp‐pattern IV) in agreement with the trend observed for the hornblende‐group amphiboles in amphibolites (Figure 8a; Ji et al., 2013; Kim & Jung, 2020; Liu & Cao, 2023). We infer from these results that the glaucophane CPO strength and type exerts a strong control on the magnitude and symmetry of the P wave seismic anisotropy in blueschists.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This transition in the Vp pattern is accompanied by increased density of the [100] and [010] crystallographic axes in the Z‐ and Y‐directions respectively that implies a transition between the type‐IV and type‐I amphibole CPOs in these samples. The magnitude of AVp percentages of the blueschists in our compilation can be broadly ordered as AVp(Vp‐pattern I) > AVp(Vp‐pattern III) > AVp(Vp‐pattern IV) in agreement with the trend observed for the hornblende‐group amphiboles in amphibolites (Figure 8a; Ji et al., 2013; Kim & Jung, 2020; Liu & Cao, 2023). We infer from these results that the glaucophane CPO strength and type exerts a strong control on the magnitude and symmetry of the P wave seismic anisotropy in blueschists.…”
Section: Discussionsupporting
confidence: 87%
“…The upper-hemisphere spherical projections of the P wave velocities display three different seismic anisotropy patterns that were previously observed in amphibolite facies deep crustal rocks (Ji et al, 2013;Liu & Cao, 2023). We describe the patterns using the terminology of Liu and Cao (2023) where Vp(X) is the velocity in the X-direction (parallel to the lineation), Vp(Y) is the velocity in the Y-direction (normal to the lineation in the foliation plane), and Vp(Z) is the velocity in the Z-direction (normal to the foliation plane). In the blueschists with the highest AVp % magnitudes, the Vp pattern is Vp(X) > Vp(Y) > Vp(Z) and is correlated to a type-I CPO in glaucophane (Figure 5a).…”
Section: P Wave Seismic Anisotropymentioning
confidence: 56%
See 2 more Smart Citations
“…Amphibole is one of the representative minerals in the middle to lower crust that has a marked influence on the rheological characteristics of the continental crust (Aspiroz et al, 2007;Christensen and Mooney, 1995;Gao et al, 1999;Tatham et al, 2008). As amphibole is also an elastically anisotropic mineral (Brown and Abramson, 2016;Ko and Jung, 2015), LPO of amphibole may contribute notably to the seismic anisotropy of the middle to lower crust (Cao et al, 2010;Kim and Jung, 2019;Ko and Jung, 2015;Liu and Cao, 2023;Tatham et al, 2008;Wang et al, 2023). Recent experimental studies have classified LPOs of amphibole into four types (type-I, II, III, and IV) and reported that temperature, differential stress, and shear strain during deformation may govern the LPO of amphibole (Kim and Jung, 2019;Ko and Jung, 2015).…”
Section: Introductionmentioning
confidence: 99%